Wavelet Based Reference Current Calculation Method for Active Compensation Systems - Gokmen, G. (Elektronika ir Elektrotechnika, 2011)
<div style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; background-image: initial; background-attachment: initial; background-origin: initial; background-clip: initial; background-color: #ffffff; margin: 8px;"> Today, active compensation systems have become more preferable compared with passive compensation systems. Performance of an active compensation system depends on current control method of the compensator as well as how this current is generated. In this study, a Discrete Wavelet Packets Transform (DWPT) based method was proposed for calculating reference current of active compensation systems and the results were compared with the currents produced from classical p-q theory. According to the obtained results, the proposed method can be used in active compensation systems without using an additional signal processing and filtering method. Ill. 12, bibl. 21, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.146